Improving Paragraph Writing Skills and Learning Activeness through a Collaborative Writing Relay Method in Elementary School - Akit, Alina; Wibowo, Setiawan Edi (Jurnal Prima Edukasia, 2025)
This study aims to improve students’ activeness and paragraph writing skills through a straw media-assisted writing relay method in Grade VI B at Rangkang Bengkayang 09 Elementary School, West Kalimantan. The research employed Classroom Action Research (CAR) involving 26 students, consisting of 13 male and 13 female students. The research instrument was a performance test. Data were collected through observations of students’ activeness and assessments of paragraph writing skills, and data analysis was conducted using a qualitative descriptive approach. The results show that students’ paragraph writing skills in Cycle I reach 76.92%, with a class average score of 73.42. In Cycle II, paragraph writing skills increased by 23.08%, achieving a 100% mastery level with an average class score of 90.42. Students’ learning activeness in Cycle I reaches 75% in the good category and increases to 100% in the very good category in Cycle II. These findings indicate that the straw media-assisted writing relay method effectively improves students’ activeness and paragraph writing skills. This study contributes to elementary language education by providing empirical evidence on the effectiveness of combining collaborative writing strategies with simple, low-cost learning media. It also offers a practical instructional model that teachers can readily implement to foster active participation and enhance writing competence, particularly in resource-limited classroom contexts.